Humidity-Activated Ammonia Sensor Based on Carboxylic Functionalized Cross-Linked Hydrogel - Yaping Song; Yihan Xia; Wei Zhang; Yunlong Yu; Yanyu Cui; Lichao Liu; Tong Zhang; Sen Liu; Hongran Zhao; Teng Fei (Sensors)
Owing to its extensive use and intrinsic toxicity, NH3 detection is very crucial. Moisture can cause significant interference in the performance of sensors, and detecting NH3 in high humidity is still a challenge. In this work, a humidity-activated NH3 sensor was prepared by urocanic acid (URA) modifying poly (ethylene glycol) diacrylate (PEGDA) via a thiol-ene click cross-linking reaction. The optimized sensor achieved a response of 70% to 50 ppm NH3 at 80% RH, with a response time of 105.6 s and a recovery time of 346.8 s. The sensor was improved for response and recovery speed. In addition, the prepared sensor showed excellent selectivity to NH3 in high-humidity environments, making it suitable for use in some areas with high humidity all the year round or in high-humidity areas such as the detection of respiratory gas. A detailed investigation of the humidity-activated NH3-sensing mechanism was conducted using complex impedance plot (CIP) measurements.